The Impact of Tadbir as a Pre-Application Treatment of Medicinal Plants on Their Chemical Profiles and Biological Activities in Traditional Persian Pharmacy - Mohammad Ali Farboodniay Jahromi; Parnia Safaee Jahromi; Mohammad Mehdi Zarshenas (Tehran University of Medical Sciences, 2024)
Based on basic traditional medicine practice, many plants undergo primary treatments to improve their pharmacological characteristics or to attenuate unwanted or unfavorable features of drugs before incorporating them into drug formulations. These treatments are called "Tadbir" in Traditional Persian Medicine (TPM). The purpose of these processes includes but is not limited to eliminating unnecessary compounds, excluding harmful properties such as toxicity and poignancy, and improving their overall natural properties and effectiveness. Here, the effect of vinegar and acetic acid treatment on three herbal specimens, including Carum carvi L. fruits (CC), Trachyspermum ammi (L.) Sprague fruits (TA), and Nigella sativa L. seeds (NS) were investigated. The treated and non-treated samples were subjected to essential oil and methanol extraction. Further, to assess the alterations in the essential oil constituents caused by Tadbir, samples were analyzed by Gas Chromatography/Mass Spectrometry (GC/MS) and HPTLC fingerprinting techniques. Total phenol and flavonoid content and DPPH free radical scavenging activity of methanol extracts were evaluated. As a result of the treatments, TA extracts showed significant rise in phenol and flavonoid contents. Total phenol content increased from 98.50±1.01 in non-treated increased to 181.20±0.27 mg GAE/g Ext. in the vinegar-treated TA fruit extract and total flavonoid showed a rise from 8.97±1.12 to 12.89±0.41 mg QE/g Ext. This may be the reason behind its lower IC50 values in DPPH free radical scavenging assay. Interestingly, Tadbir treatment of TA fruits with 4% acetic acid, lowered the IC50 value from 1019.42±75.65µg/mL in non-treated control to 274.2±17.22 µg/mL; while vinegar caused a lower degree of reduction in IC50 value (369.4±5.54 µg/mL) in DPPH free radical scavenging assay. However, CC fruit extracts, showed a decrease in phenolic content; while demonstrating an increase in flavonoids. Interestingly, phenol and flavonoid contents were significantly enhanced in treated NS seed extracts. The results of all extracts were found significantly different (p<0,05) from each other and the non-treated control. The conclusive results of the present study may partly justify the pre-application of Tadbir treatments of medicinal plants in traditional pharmacy.